2006
DOI: 10.1111/j.1600-0404.2006.00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Anosognosia after stroke: assessment, occurrence, subtypes and impact on functional outcome reviewed

Abstract: More homogeneous patient samples and consistency in the assessment methods and evaluation times would facilitate comparisons of the occurrence and the impact of anosognosia on functional outcome. New methods need to be developed for the assessment of anosognosia. These new methods should take account of the subtypes of anosognosia both at verbal and at non-verbal levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 69 publications
4
99
0
Order By: Relevance
“…Cocchini, Beschin, Cameron, Fotopoulou, & Della Sala, 2009 for left hemisphere cases; Jehkonen, Laihosalo, & Kettunen, 2006), recent neuroimaging studies have not identified a consistent pattern of brain lesion or dysfunction selectively associated with AHP. Specifically, some studies have highlighted the potential role of cortical areas such as the right insula in AHP (Berti et al, 2005;Fotopoulou et al, 2010; Baier, & Nägele, 2005;Vocat et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Cocchini, Beschin, Cameron, Fotopoulou, & Della Sala, 2009 for left hemisphere cases; Jehkonen, Laihosalo, & Kettunen, 2006), recent neuroimaging studies have not identified a consistent pattern of brain lesion or dysfunction selectively associated with AHP. Specifically, some studies have highlighted the potential role of cortical areas such as the right insula in AHP (Berti et al, 2005;Fotopoulou et al, 2010; Baier, & Nägele, 2005;Vocat et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Horizontal line indicates the cut-off score of 7 (Crawford et al, 2006) 2010). Lack of consensus amongst researchers and clinicians about the methods of assessment results in difficulties in comparing findings across different studies (Vuilleumier, 2000;2004;Adair et al, 2003;Baier & Karnath, 2005;Jehkonen et al, 2006;Vallar & Ronchi, 2006;Orfei et al, 2007;Jenkinson et al, 2011), and it may have produced contrasting findings (Cocchini & Della Sala, 2010). It seems indeed likely that while similar mechanisms may underlie anosognosia for different deficits, different causes may determine anosognosia for a specific deficit.…”
Section: Resultsmentioning
confidence: 99%
“…This is what we will refer to as "explicit anosognosia". The most common diagnostic tools are structured interviews and self-evaluation questionnaires (e.g., Jehkonen et al, 2006;Orfei et al, 2007Orfei et al, , 2010a; also summarised in Table 1). …”
Section: Methods To Assess Anosognosia For Motor Impairmentmentioning
confidence: 99%
See 2 more Smart Citations